2012
DOI: 10.1039/c2sm26043c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly scenarios of patchy colloidal particles

Abstract: The rapid progress in precisely designing the surface decoration of patchy colloidal particles offers a new, yet unexperienced freedom to create building entities for larger, more complex structures in soft matter systems. However, it is extremely difficult to predict the large variety of ordered equilibrium structures that these particles are able to undergo under the variation of external parameters, such as temperature or pressure. Here we show that, by a novel combination of two theoretical tools, it is in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…During past years, considerable effort has been dedicated to solve this intricate and challenging problem via different numerical and methodological routes [3,4,5,6,7]. In another contribution [8] we have demonstrated that a suitable combination of two complementary numerical approaches is able to provide a highly satisfactory answer to this yet open issue. To be more specific, we have combined the following two methods: (i) on one hand, an optimization technique, which employs ideas of evolutionary algorithms [9] that is able to predict efficiently and with high reliability ordered equilibrium structures at vanishing temperature; (ii) on the other hand, suitably developed Monte Carlo simulations [10,11] which allow to evaluate accurately, via thermodynamic integration, the thermodynamic properties of a particular ordered structure formed by patchy particles at finite temperature.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…During past years, considerable effort has been dedicated to solve this intricate and challenging problem via different numerical and methodological routes [3,4,5,6,7]. In another contribution [8] we have demonstrated that a suitable combination of two complementary numerical approaches is able to provide a highly satisfactory answer to this yet open issue. To be more specific, we have combined the following two methods: (i) on one hand, an optimization technique, which employs ideas of evolutionary algorithms [9] that is able to predict efficiently and with high reliability ordered equilibrium structures at vanishing temperature; (ii) on the other hand, suitably developed Monte Carlo simulations [10,11] which allow to evaluate accurately, via thermodynamic integration, the thermodynamic properties of a particular ordered structure formed by patchy particles at finite temperature.…”
Section: Introductionmentioning
confidence: 95%
“…The global enthalpy minimum for this pressure value corresponds to, as previously reported in [12,5,8], a bcc-like structure that consists of two interpenetrating, but virtually non-interacting diamond lattices. This structure emerges in two different, but closely related versions: the particles of one diamond sublattice can be located exactly in the centers of the voids of the six-particle rings making up the other diamond sublattice ("b" in Figure 1) or the positions of the particles in each sublattice can be slightly shifted against each other ("a" in Figure 1).…”
Section: Structural Variations Along Isobarsmentioning
confidence: 99%
See 3 more Smart Citations